2022
DOI: 10.1073/pnas.2122708119
|View full text |Cite
|
Sign up to set email alerts
|

Hatching is modulated by microRNA-378a-3p derived from extracellular vesicles secreted by blastocysts

Abstract: Significance Hatching from the zona pellucida is a prerequisite for embryo implantation and is less likely to occur in vitro for reasons unknown. Extracellular vesicles (EVs) are secreted by the embryo into the culture medium. Yet the role that embryonic EVs and their cargo microRNAs (miRNAs) play in blastocyst hatching has not been elucidated, partially due to the difficulties of isolating them from low amounts of culture medium. Here, we optimized EV-miRNA isolation from medium conditioned by indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 84 publications
1
26
1
Order By: Relevance
“…We find that miR-130b is significantly up-regulated during the morula and blastocysts transition, consistent with a role for miR-130b in the transition and why DGCR8-KD embryos arrest at the morula stage. Finally, a recent study documented an important role of embryonic miR-378a-3p on bovine blastocyst formation and hatching ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…We find that miR-130b is significantly up-regulated during the morula and blastocysts transition, consistent with a role for miR-130b in the transition and why DGCR8-KD embryos arrest at the morula stage. Finally, a recent study documented an important role of embryonic miR-378a-3p on bovine blastocyst formation and hatching ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hatching from the zona-pellucida is a prerequisite for embryo implantation and is less likely to occur in vitro for reasons not yet characterized. In a recent experiment (54), miR-378a-3p, secreted by individually cultured bovine embryos, is shown to promote blastocyst hatching. The next event required for pregnancy establishment in ruminants is the proper conceptus elongation prior to the initiation of conceptus attachment to the uterine epithelium (55).…”
Section: Emerging Role Of Mirna In Conceptus Hatching and Elongationmentioning
confidence: 99%
“…EVs secreted by embryos may have an effect on embryo development in addition to the presence of EVs that can affect embryo development. Relevant research has shown that the presence of miRNA-378a-3p in EVs secreted from the blastocyst stage can increase the number of embryonic trophoblast cells and inner cells, as well as improve the hatching rate ( Pavani et al, 2022 ). Surprisingly, SP-EVs may influence early embryo development.…”
Section: The Role Of Evs In Embryonic Developmentmentioning
confidence: 99%
“…EVs have been shown to improve the survival rate of frozen embryosLopera-Vasquez et al (2017) Bovine O-EVs can improve the re-expansion rate and hatching rate of frozen-thawed embryos, which may be related to O-EVs' ability to restore trophectoderm integrity and improve junctional cell contact and fluid fluxSidrat et al (2022) After vitrification, freezing, or heating, bovine O-EVs improved embryo survival, lipid content, and total cell numberLeal et al (2022) Pregnant mice's uterine cavity contains more I-EVs and higher levels of miRNA-21 than non-pregnant mice's uterine cavity. miRNA-21 may be involved in embryonic developmentI-EV Lv et al (2018)Cattle with endometritis have I-EVs that differ from normal I-EVs and are harmful to embryonic developmentWang et al (2019) EV secreted from the bovine blastocyst stage contains miRNA-378a-3p, which has been shown to increase the number of embryonic trophoblast cells and inner cells and improve hatching rate EO-EVPavani et al (2022) Mouse SP-EVs can improve blastocyst formation rate and ICM/TE index in sperm/oocyte mixed medium, as well as reduce embryonic cell apoptosis SP-EVMa et al (2022) Embryo implantation I-EVs are produced during pregnancy in pigs by both embryonic trophoblast cells and endometrial epithelial cells, but primarily by endometrial epithelial cells. I-EVs during the porcine estrus cycle or on the 9th day of pregnancy can promote embryonic trophoblast cell proliferation and migration, whereas I-EVs on the 12th or 15th day of pregnancy can inhibit embryonic trophoblast cell migration and proliferation I-EV Hu et al(2022) When endometrial epithelial cells and trophoblast cells were cultured with I-EVs from successful pregnancy pigs, the expression of ITGA5, CXCL10, and CXCL11 was significantly up-regulated, while ID2 expression was down-regulatedAhmad et al (2018) I-EVs can be used to assess early embryo implantation Li et al (2021) Ovine EM-EVs can increase IFNT production and promote trophectoderm cell proliferation EM-EV Ruiz-González et al (2015) EM-EVs have the ability to increase trophoblast cell adhesion and invasion Evans et al (2019) miRNA-100-5p in EM-EVs may promote embryonic trophoblast migration and invasion by activating FAK and JNK in embryos, as well as angiogenesis during embryo implantation Tan et al (2020a) Differential miRNAs in EM-EVs produced by progesterone treatment of endometrial epithelial cells primarily regulate PI3K/AKT, BMP, and small RNA post-transcriptional silencing Burns et al (2018) EM-EVs produced by endometrial epithelial cells co-cultured with estrogen and progesterone contained more LAMA5 than EVs produced by endometrial epithelial cells cultured with estrogen alone.…”
mentioning
confidence: 99%